2017
DOI: 10.4103/jnrp.jnrp_176_17
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Tumor of the Corpus Callosum: Clinical Characteristics, Diagnosis, and Survival Analysis

Abstract: Background:The pathologies implicate the bilateral corpus callosum that builds the butterfly pattern on axial view. These tumors have seldom been investigated for both clinical manifestations and outcome.Objective:The objective of this study was to describe the clinical characteristics and outcomes of the butterfly tumor and to identify the predictive factors associated with survival outcome.Methods:A retrospective study of 50 butterfly tumor was conducted between 2003 and 2016. The clinical characteristics, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Tunthanathip et al. [18] reported that butterfly tumor of the corpus callosum is a poor prognostic apart from his histology type. In the present case, the histopathological results confirmed diffuse astrocytoma as the correct diagnosis after the patient had died.…”
Section: Discussionmentioning
confidence: 97%
“…Tunthanathip et al. [18] reported that butterfly tumor of the corpus callosum is a poor prognostic apart from his histology type. In the present case, the histopathological results confirmed diffuse astrocytoma as the correct diagnosis after the patient had died.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, patients suffering from GBM commonly present with progressive hemiparesis, headache, nausea, and vomiting [13]. Specifically, in patients with tumors invading the corpus callosum, known as butterfly tumors, common clinical presentations are progressive headaches and hemiparesis [14]. In the male cadaver presented in this case report, the primary tumor likely originated in the right occipital lobe with subsequent anteromedial growth of the tumor into deeper brain structures such as the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…The hypervascularization of the tumor defined as the visualizing vascular structures inside a tumor (flow void sign) was reviewed. 16 The extent of resection was defined using the same definition by Vecht et al 17 Gross-total resection was defined as residual tumor seen in postoperative neuroimaging less than 5%. Subtotal resection was defined as residual tumor 5 to 25% seen in postoperative neuroimaging.…”
Section: Study Designs and Populationmentioning
confidence: 99%